Tiddas writin' up : Indigenous women and educational leadership : final report. - White, Nereda; Fredericks, Bronwyn (Australian Learning and Teaching Council, 2012)
Report of a project undertaken in 2010, designed to address the needs of Indigenous academic women in educational leadership - in particular to improve their skills in academic publishing. Through this project the women improved their knowledge of the processes and techniques of academic publishing with a focus on publishing about learning and teaching and Indigenous knowledges.